Effect of Adverse Childhood Experiences on Adult Attachment Styles and Help Seeking Behaviour Among Youth - Shruti Agarwal; Smriti Sethi (International Journal of Children, 2025)
Psychological development is deeply influenced by early environments, where personal experiences, cultural norms, and structural factors intersect. Beyond individual adversity, societal conditions shape cognitive, emotional, and social functioning, ultimately influencing attachment patterns and help-seeking behaviour in adulthood. The current study explores the influence of adverse childhood experiences on adult attachment styles and help-seeking behaviour among youth. 140 participants (70= males, 70= females) aged 18-25 years were involved in the study. The data was collected using the demographic questions and self report questionnaires, including the Adverse Childhood Experiences-International Questionnaire, the Revised Adult Attachment Scale, and the General Help-Seeking Behaviour Scale. The results indicated that there were no significant gender differences in ACEs, attachment styles, and help-seeking behaviour except for higher attachment-related anxiety in women. ACEs were correlated negatively with dependence and positively with anxiety but not with closeness. Regression analysis revealed that ACEs significantly predicted dependence and anxiety in attachment styles but had a negligible effect on help-seeking behaviour. Moreover, the limited influence of ACEs on help-seeking indicates the influence of wider structural and cultural determinants. Therefore, future studies must investigate other structural, cultural, and mediating factors to inform interventions to promote greater accessibility and utilization of mental health support.
Keywords: Adverse childhood experiences; Attachment Styles; early environments; help-seeking behaviour; youth